Frequency of renal mass complexities among patients undergoing partial nephrectomy associated with perioperative blood loss. - Haris Jameel; Mehnaz Jabeen; Rabeea Saleem; Pardeep Kumar; Asad Shahzad Hassan (International Journal of Endorsing Health Science Research, 2022)
Background: Partial nephrectomy has emerged as a standard treatment for managing small renal masses. RENAL Nephrometry score (RNS) is a widely used tool for assessing tumors, minimizing bias, and improving clinical outcomes. This study aimed to determine the frequency of various renal mass complexities based on the RENAL nephrometry score in patients undergoing partial nephrectomy and to compare the mean blood loss in these patients. Methodology: The cross-sectional study was conducted at the Department of Urology, Sindh Institute of Urology & Transplantation, Karachi- Pakistan. Perioperative blood loss after partial nephrectomy was observed in all cases, and patients had their RENAL nephrometry score determined before surgery. The patient's baseline demographic data, including age, gender, and body mass index (BMI), was recorded using a pre-designed Proforma. Results: According to the RNS, there were 33(52.4%) patients with moderate complexity, followed by 19(30.25%) and 11(17.4%) who had severe and mild complexity, respectively. Furthermore, there was a significant difference in the mean blood loss among the three groups (p=0.025). Among the cofounders, age, BMI, and male gender significantly affected mean blood loss in different RNS groups (p<0.05). Conclusion: There was a high frequency of moderate renal complexity among the studied patients based on the RNS. A significant difference in the mean blood loss was observed among the patients with mild, moderate, and severe complexity.